The Mediating Role of The Business Value and An Organizational Performance (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This study examines the mediating role of the knowledge management in SMEs and the human resource-basedentrepreneurship between an organizational performance and business value. This research was collected responses using aquestionnaire from a sample of 223 business doers SMEs in Indonesia. Structural Equation Modeling AMOS is used toanalyzed data collected. The findings show that the direct influence of the knowledge management on business value higherthan an organizational performance. The results show that the knowledge management and the human resource-basedentrepreneurship mediate the relationship between explicit knowledge, tacit-knowledge and the business value stronger thanan organizational performance. The good entrepreneurial spirit that refers to management-based entrepreneurship andsupported by adequate the knowledge management, it will be easy to manage a business value and improve an organizationalperformance.